Urgensi Manajemen Pendidikan Berbasis Nilai-Nilai Kearifan Lokal Tri Hita Karana dalam Meningkatkan Komitmen Organisasional Guru - Kadek Hengki Primayana; Ketut Bali Sastrawan (STAHN Mpu Kuturan Singaraja, 2021)
Education is a pillar of the nation's progress, becoming a developed nation is certainly an aspiration to be achieved by every country in the world. It is common knowledge that the progress of a country is influenced by educational factors. Education is the process of printing the nation's next generation of quality. Therefore, educating the nation's life is made one of the national goals that must be fought for by all parties. Schools based on local wisdom are in tune with the government's efforts to preserve culture in Indonesia. Currently, the younger generation of the nation's successors are starting to leave their own culture and switch to western culture. The thing that tarnished Indonesia's name was the events of the past few years. One of the causes of this incident is that the younger generation does not want to learn about their own culture.